The Impact of School Climate and Social Support on Bullying Tendencies in Vocational High School Students - Ningsih, Anjela Ulfa; Juliawati, Dosi; Kholidin, Farid Iman (STAI Auliaurrasyidin Tembilahan, 2025)
Bullying is aggressive behavior involving a power imbalance between the victim and the perpetrator. A negatively perceived school climate can increase maladaptive behaviors, including bullying. Social support, encompassing a sense of being valued, loved, and cared for also play a critical role in reducing bullying. This quantitative study aims to examine the influence of school climate and social support on bullying tendencies among vocational high school students. Using a cross-sectional online survey, 343 students participated as respondents. Multiple regression analysis revealed an F-value of 13.757 with a significance level of 0.000 (<0.05), indicating a significant influence of school climate and social support on bullying tendencies. The findings suggest that despite a generally high level of social support (mean = 34.57, SD = 2.99) and school climate (mean = 37.47, SD = 3.47), some students still experience moderate levels in these variables. Additionally, a notable number of students continue to report high bullying tendencies, highlighting the need for targeted interventions to improve school environments and strengthen social support systems.